2021
DOI: 10.1097/pai.0000000000000969
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of an Intestinal Neuroendocrine/Non-neuroendocrine Neoplasm (MiNEN) Reveals MLH1 Methylation-driven Microsatellite Instability and a Monoclonal Origin: Diagnostic and Clinical Implications

Abstract: Mixed neuroendocrine/non-neuroendocrine neoplasms (MiNEN) are rare mixed epithelial neoplasms in which a neuroendocrine component is combined with a non-neuroendocrine component. Here, we provide the clinical, pathologic, and molecular report of a 73-year-old-man presenting with an intestinal MiNEN. The lesion was composed of a well-differentiated G3 neuroendocrine tumor and a colloid adenocarcinoma. The molecular characterization was performed using a multigene nextgeneration sequencing panel. The neoplasm di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The molecular features of MiNEN (at least of those with adenocarcinoma components) appear to be more closely related to those of non-neuroendocrine adenocarcinomas than to those of NECs, as BRAF, KRAS and APC mutations are common while RB1 mutations are sparse and TP53 mutations occur in lower frequency compared to NECs [35]. Recent publications have also described microsatellite instability and ATRX mutations in MiNEN [41][42][43]. However, the genetic landscape of MiNEN is heterogenous and complex and remains to be elucidated.…”
Section: Mixed Neuroendocrine-non-neuroendocrine Neoplasms (Minen)mentioning
confidence: 99%
“…The molecular features of MiNEN (at least of those with adenocarcinoma components) appear to be more closely related to those of non-neuroendocrine adenocarcinomas than to those of NECs, as BRAF, KRAS and APC mutations are common while RB1 mutations are sparse and TP53 mutations occur in lower frequency compared to NECs [35]. Recent publications have also described microsatellite instability and ATRX mutations in MiNEN [41][42][43]. However, the genetic landscape of MiNEN is heterogenous and complex and remains to be elucidated.…”
Section: Mixed Neuroendocrine-non-neuroendocrine Neoplasms (Minen)mentioning
confidence: 99%
“…On the other hand, BRCA2 has been explicitly altered in the neuroendocrine area. Although the latter observation suggested that BRCA2 could be a potential new target for MiNEN, the lack of this alteration in the nonneuroendocrine part of the tumor requires further consideration concerning intratumor heterogeneity[ 90 ].…”
Section: Organ-specific Clinicopathological Findingsmentioning
confidence: 99%